Factors Related to Traffic Accidents for Two-Wheel Motorcycle Riders - Sugiarto Sugiarto (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2023)
Two-wheeled vehicle traffic accidents in Jambi City were from 327 cases to 358 cases. In 2021 it is known that Kota Baru District is the sub-district with the highest number of two-wheeled accidents, which is 75 cases. This study aims to determine the factors associated with traffic accidents on two-wheeled motorcycle drivers in Jambi City. The study used a cross sectional design. This research was conducted in Jambi City from 11 May to 29 June 2022. The sample of the research was 97 motorcycle riders in Jambi City. The sampling technique used accidental sampling technique. The research instrument is a questionnaire. The data were analyzed using the chi square test. A total of 36.1% of respondents had experienced a traffic accident, 39.2% of respondents with poor driving behavior, 38.1% of respondents with poor vehicle factors, 40.2% of respondents stated that environmental factors were not good and 34.0% of respondents not good at using personal protective equipment. The results of the bivariate analysis showed that there was a relationship between driving behavior (p = 0.038), vehicle factors (p = 0.000), environmental factors (p = 0.030) and the use of personal protective equipment (0.040) with traffic accidents on two-wheeled motorcycle riders.